Aplicação da tabela de vida das culturas às pragas de Phaseolus vulgaris L em quatro níveis de adubação. II- em áreas de baixa fertilidade - Della Lucia , Terezinha M C; Chandler , Leland; Dias Casali , Vicente W; Domingos Galvão , José; H Freire , José Alberto; da Costa , Liovando Marciano (Revista Ceres, 2025)
Two plantings of beans (Phaseolus vulgaris L., cv. ‘Ricobaio’) were made, one during the dry season and one during the rainy, in an area of low soil fertility located 8 km south of the Agronomy Experimental Area of the Federal University of Viçosa.